القدس محور الصراع: سيناريوهات التهويد والتصعيد - حطيط، رولا جميل (مركز المبادرة الاستراتيجية, 2022)
تنطلق الصهيونية من عبارة "شعب الله المختار" حيث الاعتقاد بأن اليهود شعب مفضل على سائر الشعوب، وأن لهم حقا تاريخيا في فلسطين "الأرض الموعودة" ومن هذا كان شعار الكيان الصهيوني "حق الاستيطان في كل مكان" ففرض بالقوة، سياسته التوسعية المنتهجة منذ قيام دولته عام 1948، وبها طال استيطانه أراض عربية أخرى عقب "حرب 1967" وسياسة الاستيطان الصهيوني في الأراضي الفلسطينية المحتلة هو تعبير عن الاستراتيجية الصهيونية في الهيمنة على المنطقة، إذ يمنح الكيان لنفسه حرية وصول الاستيطان لبلاد أخرى، هذا بالإضافة إلى أن الطبيعة القانونية الخاصة لهذا الاستيطان وما يتلقاه من دعم دولي خاصة "أمريكي" يشكلان العارض الأساس للتخلص منه، ما يجعل القضية الفلسطينية أعقد القضايا الاستعمارية التي عرفها التاريخ بحيث يستعصى حلها على غرار القضايا الاستعمارية. فلا تزال تشكل مركز اهتمام المجتمع الدولي بأسره لما للصراع الإسرائيلي -الفلسطيني من تأثير على السلم بالمنطقة وعلى السلم الدولي. من هنا كانت أهمية الموضوع خاصة وأن القضية الفلسطينية في تطور مستمر نتيجة السياسة الاستيطانية التوسعية التي تمارسها دولة الاحتلال حيث تصاعد الصراع الإسرائيلي الفلسطيني القائم سيما في مدينة القدس وما لها من أهمية على مستوى الصراع. والوضع الراهن بأبعاده الخطيرة من دواعي الضرورة للبحث في الموضوع بهدف التوصل إلى مقاربة الوضع القائم وإيجاد حل يتواءم وطبيعة القضية برفع مختلف ملابسات المسألة رغم كونها تمثل قضية عادلة لابد وأن تنصف يوما. من هذا المنطلق كان اختيار الموضوع آملين بهذا الجهد المتواضع المزيد من الإضاءة على الحقيقة الكامنة أساسا في الحقوق الشرعية الثابتة للشعب الفلسطيني، رغم ما انتهك منها وما استجد في القضية عامة. ولدراسة الموضوع اعتمدنا المنهج التحليلي الوصفي والمنهج التاريخي، وذلك في رصد السياق التاريخي الذي شهدته مدينة القدس تزامنا مع تحليل الأحداث التي تتسارع بشكل يومي في هذه المدينة. وتمت مقاربة موضوع البحث من خلال الإضاءة على العناوين التالية: رمزية القدس وأشكال التهويد فيها، مسار قرار ترامب في جعل القدس عاصمة "إسرائيل" المقاومة في القدس، وخلاصة. Zionism stems from the phrase "God's chosen people", where the Jews are considered a preferred people over all peoples, and that they have a historical right to Palestine, the "promised land", hence the slogan of the Zionist entity "the right to settle everywhere", and imposed its expansionist policy by force Since the establishment of its state in 1948, there has been prolonged settlement of other Arab lands after the "1967 war". The Zionist settlement policy in the occupied Palestinian territories is an expression of the Zionist hegemony strategy in which the entity gives itself the freedom to expand the settlements to other countries. This is in addition to the international support it enjoys, especially the “American” support, which constitutes the main objection to getting rid of it, which makes the Palestinian issue one of the most complex colonial issues known to history, as it is difficult to solve it in a similar way. to old colonial issues. It remains the focus of attention of the entire international community because of the impact of the Israeli-Palestinian conflict on peace in the region and its repercussions on international peace. Hence the importance of the issue, especially since the Palestinian issue is in constant development as a result of the expansionist settlement policy practiced by the occupying state, as the existing Israeli-Palestinian conflict, especially the city of Jerusalem, has escalated and its importance. The current situation, with its dangerous dimensions, is one of the reasons for the necessity of discussing the issue with the aim of reaching an approach to the current situation and finding a solution commensurate with the nature of the issue by raising the different circumstances. Although it is a fair issue. From this point of view, we chose the topic in the hope that this modest effort will shed more light on the truth that is fundamentally rooted in the inalienable legal rights of the Palestinian people, despite what was violated and what happened in the case in general. To study the subject, we adopted the analytical descriptive approach and the historical approach, in observing the historical context of the city of Jerusalem, in conjunction with analyzing the accelerating events on a daily basis in this city. The subject of the research was addressed by highlighting the following titles: the symbolism of Jerusalem and the forms of Judaization therein, the course of Trump's decision to make Jerusalem the capital of "Israel". Resistance in Jerusalem and a conclusion.
Keywords: الاحتلال الصهيوني -- القضية الفلسطينية -- الصراعات السياسية -- المقاومة الفلسطينية -- القدس